The Interpreter Shamus Al- Deen Ibn Al – Labban Biography And His Cultures - Abdulwhab Mahmoud, Omar (Opción, 2019)
This research tackles one of this nations scholar , was not studied by other researchers . Many of us know nothing about his life , books , arguments in a manner Like other scholars of this nation . Therefore , it is the task of this study , in a response to the favour of Ibn al – Labban on us , to reveal his works .This study deals with him through four sections . section one investigate his biography , including six sub divisions regarding his name date of birth , Life , his father life , death , and finally , this section concludes with the embarrass- ment which might a reader face in differentiation between Ibn al – labban and the other respectiful scholars , because of the great similarity between them in more than one aspect. Section two concentrates on his teachers , students and his descendants , so that efforts have been made to list names of his teachers , names of his student and his descendants who were stated by their researcher as descendants of Ibn al – labban to give a clear picture about his family , in the mind of the reader. The other section three section three devotes on his works , books concerning the printed ones , the manuscripts , or the missing ones which we have nothing about them just the title or the subject , in addi- tion to his argument in interpretation , and some of poems and laments which are ascribed to him. As regarding to the latter research , it is allocated for names mentioned similar to his name with relation of a quarter , mosque or religious scientist . this is achieved in order to avoid confusion between him and others .